Hypertension among Haitians Living in the Bahamas - Mazzeo, John G. (International Journal of Bahamian Studies, 2013)
For many Haitians in the Bahamas, migration and the process of adapting to life in an often hostile environment creates stress and may be correlated with high blood pressure. This study examines the social determinants of hypertension among Haitians in the Bahamas by exploring how experiences of migration create stress that is believed to cause high blood pressure. The Haitian explanatory model of high blood pressure, tansyon, explains the relationships between variables such as diet, stress, and poverty, and the blood. Research was conducted in several Haitian communities in New Providence and Abaco using ethnographic methods such as interviews and participant observation. Information about hypertension was also obtained during community blood pressure education workshops conducted in collaboration with Haitian community associations. This study offers valuable insights for public health efforts in the Bahamas on the issue of hypertension in the Haitian community. This study is relevant to researchers studying the connections between hypertension and migration for populations originating from less developed countries.